Numerical experiments on the determination of unsteady state temperature distribution in a solid propellant rocket motor. - Laura, P. A. A.; Sánchez Sarmiento, G.; Olivetto, M. E. (Elsevier, 1979)
Fil: Laura, P. A. A. Comisión Nacional de Energía Atómica; Argentina